Cervical ectopics: less can be more. (9th August 2012) - Stott, Daniel; Eissa, Asma; Zaedi, Khaled
Abstract : A 27-year-old woman with a positive urinary-pregnancy test, complaining of slight vaginal bleeding and some diffuse lower abdominal pain, presented to the emergency gynaecology unit at the Royal Free Hospital. Her initial ultrasound scan was inconclusive, and so serial serum beta human chorionic gonadotropin (hCG) blood tests were carried out. These demonstrated a suboptimal increase. A second transvaginal ultrasound (TVUS) was therefore performed, which showed a live cervical ectopic pregnancy. The patient, who remained haemodynamically stable, was admitted. She was treated with intramuscular methotrexate. She was given a second dose of methotrexate after 1 week, since her beta hCG levels did not demonstrate a satisfactory fall. A rapid decrease in serum hCG was then observed and the patient was then discharged. An outpatient TVUS was normal. The patient remained well throughout her treatment, never suffered any profuse vaginal bleeding, and thus surgical intervention was avoided.